2022
DOI: 10.3390/plants11202690
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effects of Plant Extracts from Salvia deserta Schang. and Salvia sclarea L.

Abstract: Medicines, their safety, effectiveness and quality are indispensable factors of national security, important on a global scale. The COVID-19 pandemic has once again emphasized the importance of improving the immune response of the body in the face of severe viral infections. Plants from the Salvia L. genus have long been used in traditional medicine for treatment of inflammatory processes, parasitic diseases, bacterial and viral infections. The aim of the current study was to evaluate the immunomodulatory effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…On the contrary, when LPS-stimulated macrophages were treated with the same sage extracts, the level of IL-1β secretion in macrophages was remarkably inhibited [119]. The data obtained by us comply with those of other scientists, who demonstrated that several groups of plant secondary metabolites (phenolic compounds, terpenes, polysaccharides) impact the functional activity of macrophages [120]. For instance, S. miltiorrhiza extract is reported to inhibit the production of NO, PGE2, IL-6, IL-1β, and TNF-α, and chemokines expression, RANTES, CX3CL1, and CX3CR1, as well as inflammatory mediators like TLR-4 and 11β-HSD1 in LPS-stimulated RAW 264.7 macrophages [121].…”
Section: Anti-inflammatory Activitysupporting
confidence: 89%
See 2 more Smart Citations
“…On the contrary, when LPS-stimulated macrophages were treated with the same sage extracts, the level of IL-1β secretion in macrophages was remarkably inhibited [119]. The data obtained by us comply with those of other scientists, who demonstrated that several groups of plant secondary metabolites (phenolic compounds, terpenes, polysaccharides) impact the functional activity of macrophages [120]. For instance, S. miltiorrhiza extract is reported to inhibit the production of NO, PGE2, IL-6, IL-1β, and TNF-α, and chemokines expression, RANTES, CX3CL1, and CX3CR1, as well as inflammatory mediators like TLR-4 and 11β-HSD1 in LPS-stimulated RAW 264.7 macrophages [121].…”
Section: Anti-inflammatory Activitysupporting
confidence: 89%
“…In our experiments, extracts of S. deserta and S. sclarea obtained by conventional and ultrasonic-assisted extraction significantly reduced the production of pro-inflammatory cytokine TNF-α in both unstimulated and LPS-stimulated peritoneal macrophages. At the same time, it had a strong stimulatory effect on the release of IL-1β in previously unstimulated macrophages remarkably in comparison to control [120]. On the contrary, when LPS-stimulated macrophages were treated with the same sage extracts, the level of IL-1β secretion in macrophages was remarkably inhibited [119].…”
Section: Anti-inflammatory Activitymentioning
confidence: 88%
See 1 more Smart Citation